The papermaker's companion : the ultimate guide to making and using handmade paper - Hiebert, Helen, 1965- (North Adams, MA. : Storey Publishing, 2000)
This valuable reference covers everything, from the basics to more advanced techniques like shaped sheets, embossing, laminating, and watermarking. Included are extensive step-by-step instructions on processing pulp, building papermaking equipment, and making paper-based projects like cards, lamp shades, and sculpture.
-- part 1. Papermaking basics: Getting equipped. Collecting and preparing the fiber. Beating pulp. Using additives. Making paper -- part 2. Papermaking techniques and projects: Pulp painting. Laminating and embedding. Decorating with inclusions. Embossing. Making shaped sheets. Watermarking. Casting. Using armatures. Pulp spraying. Children's projects.
Includes bibliographical references (pages 206-207) and index.
Keywords: Paper, Handmade -- Handbooks, manuals, etc